Inventory of Personal Factors Influencing Conditioned Pain Modulation in Healthy People: A Systematic Literature Review. Issue 6 (26th May 2015) - Hermans, Linda; Van Oosterwijck, Jessica; Goubert, Dorien; Goudman, Lisa; Crombez, Geert; Calders, Patrick; Meeus, Mira
Abstract: Background: Conditioned pain modulation (CPM) is believed to play an important role in the development and exacerbation of chronic pain, because dysfunction of CPM is associated with a shift in balance between pain facilitation and pain inhibition. In many patients with central sensitization, CPM is less efficacious. Besides that, efficacy of CPM is highly variable in healthy people. Consequently, it seems that several individual variables may influence CPM. A systematic review examining personal factors influencing CPM was conducted. Methods: This systematic review follows the PRISMA guidelines. "Pubmed" and "Web of Science" were searched using different synonyms of CPM. Full‐text clinical reports addressing the influence of personal factors on CPM in healthy adults were included. Checklists for RCTs and case–control studies provided by the Dutch Institute for Healthcare Improvement (CBO) and the Dutch Cochrane Centre were utilized to assess methodological quality. Levels of evidence and strength of conclusion were assigned using the CBO guidelines. Results: Forty‐six articles were identified that reported the influence of personal factors on CPM. Quality assessment revealed 10 studies with a methodological quality less than 50% wherefore they were excluded (21.8%), resulting in a general total methodological quality score of 72.5%. Overall younger adult age, male gender, ovulatory phase, positive expectations, attention to the conditioning stimulus, and carrier of the 5‐HTTLPR long allele result in better CPM. Conclusion: It is advised for future studies to take these factors into account. Further research regarding the influence of oral contraceptives, catastrophizing, information about conditioning stimulation, distraction, physical activity, and genetics on CPM magnitude is required.